Telaahan Literatur Tentang Program Perawatan Pesawat Udara - Minda Mora (WARTA ARDHIA, 2012)
Maintenance is one of the most important thing in aviation. Maintenance is the process where a systems designed-in level of failure resistance is restored to or as close as economic viable to the most adequate level of the design. In order to conduct maintenance in the right way, each aircraft is required to have a Maintenance Program (MP). There are three main actors relating to the initial development of the MP, which are the manufacturer, the Industrial Steering Committee (ISC) and the Maintenance Review Board (MRB). In the manufacturers, PPH (Policies and Procedures Handbook) process for developing the initial MP is clearly described. The PPH is prepared by the manufacturer and presented to the ISC (Industrial steering committee) for review and approval. ISC then forwards it to the MRB chairpersons and other regulatory authorities for acceptance.Based on MRB review, the manufacturer develop Maintenance Review Board Report (MRBR) and Maintenance Planning Document (MPD). When introducing a new fleet of aircraft into the operator, there is no experience and the organization must follow the MRBR (Maintenance Review Board Report) and MPD (Maintenance Planning Document) when setting up their own MP. It is the operator’s responsibility to ensure that their MP is up to date. When a new revision of the MRBR and MPD is released the operator should incorporate the alterations into their MP and update their maintenance system and make the revision active at next suitable opportunity. The next suitable opportunity would be before next major base input or c-check.Perawatan pesawat udara merupakan salah satu unsur penting dalam penerbangan. Perawatan adalah semua kegiatan yang dilakukan untuk mempertahankan pesawat udara, komponen-komponen pesawat udara dan perlengkapannya dalam keadaan laik udara termasuk inspeksi, reparasi, servis, overhaul dan penggantian part. Untuk dapat melakukan perawatan dengan benar, maka setiap pesawat udara diharuskan memiliki Program Perawatan. terdapat 3 (tiga) pihak yang terlibat dalam penyusunan awal Program Perawatan, yaitu pabrikan pesawat udara, the Maintenance Review Board (MRB), dan the Industrial Steering Committee (ISC). Pabrikan berkewajiban membuat Policy and Procedures Handbook (PPH) yang berisi informasi lengkap dan jelas tentang proses penyusunan Program Perawatan Pesawat Awal. PPH kemudian diserahkan kepada ISC yang berkewenang untuk melakukan peninjauan terhadap PPH dan apabila telah memenuhi persyaratan maka ISC mengeluarkan persetujuan terhadap PPH (approval). Selanjutnya, ISC menyerahkan PPH kepada MRB untuk evaluasi dan analisis lebih lanjut. Berdasarkan evaluasi dan analisis MRB, pabrikan membuat Maintenance Review Board Report (MRBR) dan Maintenance Planning Document (MPD). MRBR dan MPD merupakan panduan bagi operator pesawat udara untuk melakukan perawatan pesawat udara dan membuat Program Perawatan pesawat udara sendiri. Namun, operator berkewajiban untuk memperbahatui Program Perawatannya apabila terdapat perubahan MRBR dan MPD dari pabrikan.